(untitled) (Latakia University Journal -Biological Sciences Series, 2017)
تم تقصي الأثر المتبقي للمبيدين imidacloprid وacetamiprid من مجموعة المبيدات النيونيكوتينيةNeonicotinoids في ثمار البندورة. جمعت العينات قبل الجني مباشرة من بيوت بلاستيكية في محافظة طرطوس، كما أخذت عينات عشوائية من ثمار البندورة من الأسواق في حمص وطرطوس واللاذقيةومن مراكز تجميع الخضار والفواكه في طرطوس.بغية تحديد الأثر المتبقي لهذين المبيدين والذي يمكن أن يصل إلى المستهلك. أجريت التحاليل باستخدام جهاز الكروماتوغرافيا السائلة عالية الأداء(HPLC)High Performance Liquid Chromatographyباعتماد عمود Teknokroma C-18 (250mm* 4.6mm). تراوحت تراكيز المبيد acetamiprid بين 0.005-0.5 مغ/كغ والمبيد imidacloprid بين 0.01-0.48 مغ/كغ. احتوى 13.6% من عينات البندورة في البيوت البلاستيكية ومن مراكز التجميع والأسواق على أثر متبقي من مبيد acetamiprid فوق الحدود العليا المسموحةmaximum residue level (MRL) من قبل منظمة الأغذية والزراعة العالمية (FAO)Food And Agriculture Organizationومنظمة الصحة العالمية(WHO)World Health Organizationومن الاتحاد الأوروبي، بينماكان محتوى العينات من المبيد imidacloprid ضمن الحدود المسموح بها. This study quantitatively measured the residues of two Neonicotinoids (acetamiprid&imidacloprid) in greenhouse tomato fruits. Samples were collected before harvest from greenhouses in Tartous and Latakia governorates,also random samples were collected from traditional markets in Hims, Tartous and Latakiaand market halls in Tartous to determine the insecticides residues which reach the customers. The analysis were performed using High Performance Liquid Chromatography (HPLC) with column Teknokroma C-18 (250mm* 4.6mm – 5 μm). The concentrations varied between 0.005-0.5 mg/Kg for acetamiprid and between 0.01-0.48 mg/Kg for imidacloprid. The tested greenhouse tomatoes and random samples showed 13.6% contamination with acetamiprid above the maximum residue level (MRL)according to the Food And Agriculture Organization (FAO), World Health Organization (WHO) and the European Union legislationswhile all the tested samples for imidacloprid have concentrations below MRL limits, with imidacloprid having the highest detection rate among all samples.